English and Vietnamese business complaint letters in the light of systemic functional grammar / Cao Thi Thu Huyen; NHDKH Ph.D Do Kim Phuong - Cao, Thi Thu Huyen
It cannot be denied that business correspondence plays an important role in business communication. In Vietnam, customers have gradually had the tendency to write complaint letters; however, this has not become their habit and a number of customers, in fact, still hesitate to do this although they know they have the right to do. In the hope of working out some solutions to help Vietnamese people as well as Vietnamese students, to some extent, overcome their difficulties in writing business complaint letters, the study is an attempt to analyze some basic features of business complaint letters from Functional Perspectives. The study aims at analyzing one kind of business letters - business complaint letters in both English and Vietnamese in terms of transitivity, mood, and cohesion in the light of Systemic Functional Grammar. The investigation and analyses have been based on the data taken in 30 business complaint letters written by both native speakers of English and Vietnamese (15 in English and 15 in Vietnamese; both types of letters are numbered from 1 to 15 for more convenient reference) which presume to be sufficient data. Thus, the thesis is conducted to help Vietnamese learners and teachers to write and teach writing effective business complaint letters in English. The main methods employed in this study are descriptive, analytic, and contrastive. Based on the results of analysis, similarities and differences are identified and explained. Therefore, we hope that these findings will be a helpful source for the teacher and learner in the course of teaching and studying writing business complaint letters